Here's the wrap on packaging - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
It contains: packaging has to conform to certain rules (such as showing the exact mass or volume of the contents). This is now spreading towards smaller portions, for an individual's or a day's consumption (such as individually packaged stock...